ANALISIS VARIABILITAS GENETIK DAN KOEFISIEN LINTAS BERBAGAI KARAKTER AGRONOMI DAN FISIOLOGI TERHADAP HASIL BIJI DARI KERAGAMAN GENETIK 54 ASESI JAGUNG ASAL INDONESIA TIMUR - Boer, Dirvamena (Jurnal Agroteknos, 2011)
The experiment was conducted to evaluate genetic variability, heritability, genetic gain, genetic and phenotypic correlation using path-coefficient analysis for some agronomic and physiology characters of 54 accessions of maize from East Indonesia.  The experiment was  arranged in  a  randomized completely block  design  with  tree  replications using  54 accesions.   Characters observed were plant high/TTM, number of leaves/JDT, number of leaves  above  ear/JDA,  Length  of  branches  part  of  tassel/PTM, length  of  peduncle/PMA, length of ear/PTO, diameter of ear/DTO, number of kernel rows per ear/JBT, flowering time of  male  flower/UBJ,  flowering  time  of  female  flower/UBB,  maturity  time/UMT,  seed size/UBJ, leaf area index/ILD, and seed yield/BBJ.   The result of the experiment indicated that genetic variability, broadsense heritability and genetic gain for all agronomic and phisiology characters were high.  Maize seed yield improvement can be effectively done by selecting for number of leaves, maturity time and seed size. Keywords:    Genetic variability, heritability, correlation, path-coefficient analysis